Method for identifying urban sludge moisture occurrence state by using extracellular polymeric substance

By using the hydrophilic and hydrophilic components of extracellular polymers to identify the state of moisture in the sludge, the problem of poor accuracy of sludge moisture distribution testing in the prior art is solved, and the sludge dehydration efficiency and detection accuracy are improved. Improvement provides a scientific basis for the optimization of sludge treatment technology.

CN119492595APending Publication Date: 2025-02-21HARBIN INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411614592.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing water distribution testing methods in sludge have poor accuracy, making it difficult to accurately identify the distribution status of different types of water in sludge, which affects the improvement of sludge dehydration efficiency.

Method used

By using the hydrophilic and reproducible components of extracellular polymers, the allocation of moisture in urban sludge is identified. The specific steps include centrifugation, adding ammonia water to shock, determining the total organic carbon content or the ratio of hydrophobic and hydrophilic organic matter, etc., and then Calculate the content of free water, chemically bound water and mechanically bound water.

Benefits of technology

It realizes accurate identification of the sludge moisture storage state, significantly improves the accuracy of sludge dewatering performance detection, provides a scientific basis for the optimization of sludge dewatering process, and promotes sludge treatment technology toward efficient, intelligent and precise direction develop.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119492595A_ABST
    Figure CN119492595A_ABST
Patent Text Reader

Abstract

The invention discloses a method for identifying the occurrence state of water in urban sludge by using extracellular polymeric substances, relates to a method for identifying the occurrence state of water in sludge, and aims to solve the technical problem that the existing method for testing the distribution of water in sludge is poor in accuracy, and the method comprises the following steps of: extracting an extracellular polymeric substance solution of urban sludge, and testing the total organic carbon content in the extracellular polymeric substance solution; or the ratio of the hydrophobic organic matter to the hydrophilic organic matter, or the content of protein, or the content of polysaccharide, or the content of humic acid, or the fluorescence intensity value of tryptophan protein, or the fluorescence intensity value of tyrosine protein, or the proportion of alpha-helix of a protein secondary structure, or the proportion of beta-corner, or the proportion of beta-helix of a protein secondary structure; the content of the free water, the chemical bound water and the mechanical bound water is calculated according to the relation curve between the parameters and the free water and the chemical bound water, the quantification precision is high, the detection precision of the sludge dewatering performance is improved, and support is provided for the sludge dewatering process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of urban sludge dehydration, and in particular to a method for accurately identifying the water content state of sludge by the hydrophilic and hydrophobic components of extracellular polymers. Background Art

[0002] Sludge is an inevitable byproduct of sewage biological treatment. Urban sludge contains a large amount of water and is accompanied by complex pollutants such as heavy metals, antibiotics, and pathogens. If it is not properly disposed, it will cause serious economic burdens and environmental risks. Therefore, seeking an effective sludge treatment method has become an urgent problem to be solved.

[0003] Sludge dewatering is one of the core steps in the sludge treatment and disposal process, which can significantly reduce the volume of sludge, reduce transportation costs, and reduce the generation of leachate in landfills. However, the organic matter in the sludge captures a large amount of water, namely bound water, through its biopolymer network, and its properties are significantly different from those of free water. According to the interaction between water and solid components, bound water can be further divided into mechanically bound water and chemically bound water (referred to as bound water). Due to the steric hindrance effect of microbial aggregates and the high affinity between extracellular polymers and water, the accurate definition and identification of different types of water in sludge is extremely complex, which has become the main factor hindering the improvement of dewatering efficiency.

[0004] The test methods for the distribution of water in sludge include heat drying method, dilatometer method, centrifugal sedimentation method, thermogravimetric analysis method, etc. However, these methods generally have the problems of destroying the sample structure during the test, poor reproducibility of the results, and large differences in the results between different methods. Therefore, it is urgent to develop a method to accurately identify the water state of sludge and determine an effective method for sludge dehydration based on various water states. Summary of the invention

[0005] The present invention aims to solve the technical problem of poor accuracy of existing methods for testing the distribution of water in sludge, and to provide a method for identifying the water content state of urban sludge by using extracellular polymers.

[0006] The method of the present invention for identifying the water content state of urban sludge by using extracellular polymers is carried out according to the following steps:

[0007] 1. Take the sludge from the secondary sedimentation tank of the urban sewage treatment plant, store it in a refrigerator at 4℃ and let it settle for 24 to 72 hours, then centrifuge the settled sludge, discard the supernatant, and take the sludge sediment at the bottom of the centrifuge tube as the test sample;

[0008] 2. Add ammonia water to the test sample, place it in a shaker and shake at a constant temperature, and take the supernatant, which is the extracellular polymer solution;

[0009] 3. Test the total organic carbon content of the extracellular polymer solution. The total organic carbon content is represented by x in mg / gVS. The free water content in the urban sludge is represented by y. 1 =-0.0147x+5.4537, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 =0.0185x+1.0302, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 , where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0010] Alternatively, the ratio of hydrophobic organic matter to hydrophilic organic matter in the test extracellular polymer solution is expressed as a, dimensionless; the free water content in urban sludge is expressed as y 1 =1.0268a+0.8918, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 =-1.3946a+6.9884, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0011] Alternatively, the protein content in the test extracellular polymer solution is b, in mg / g VS; the free water content in the urban sludge is y 1 = 0.0333b + 1.6203, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 =-0.0484b+6.1425, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0012] Alternatively, the content of polysaccharides in the extracellular polymer solution c is measured in mg / g VS; the content of free water in urban sludge is measured in y 1 =-0.0874c+5.8395, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 = 0.1241c + 0.0986, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0013] Alternatively, the content of humic acid in the test extracellular polymer solution is measured in mg / g VS; the content of free water in the municipal sludge is measured in y 1= -0.0119d+4.0989 calculation, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 =0.0155d+2.6871, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0014] Alternatively, the fluorescence intensity value e of tryptophan proteins in the test extracellular polymer solution is dimensionless; the free water content in urban sludge is expressed as y 1 =-0.0262e+5.8598, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 = 0.0362e + 0.1727, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0015] Alternatively, the fluorescence intensity value f of tyrosine proteins in the test extracellular polymer solution is dimensionless; the free water content in urban sludge is expressed as y 1= 0.0569f+1.1071 calculation, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 =-0.072f+6.5101, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0016] Alternatively, the proportion of protein secondary structure α-helix in the test extracellular polymer solution is g, in %; the content of free water in urban sludge is y 1 =-0.1335g+5.9203, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 = 0.1716g + 0.362, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0017] Alternatively, the ratio of protein secondary structure β-turn in the test extracellular polymer solution is h, in %; the free water content in urban sludge is y 1 =-0.1794h+7.093, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 =0.2241h-1.0014 calculation, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 Indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge;

[0018] Alternatively, the ratio of α-helix / (β-sheet + random coil) in the secondary structure of proteins in the test extracellular polymer solution is j, dimensionless; the free water content in urban sludge is y 1= -4.0478j+4.7488 calculation, where y 1 It indicates the content of free water in %; the content of chemically bound water in urban sludge is expressed in y 2 =4.7323j+2.0585, where y 2 It indicates the content of chemically bound water in %, and the content of mechanically bound water in urban sludge is expressed in y 3 =100-y 1 -y 2 Calculate, where y 3 It indicates the content of mechanically bound water, thus knowing the moisture state of urban sludge.

[0019] Furthermore, the centrifugal separation in step 1 has a rotation speed of 3000-5000g.

[0020] Furthermore, in step 2, the ratio of the sludge precipitate to the ammonia water with a mass percentage concentration of 24% to 26% is 1g: (1 to 3)mL.

[0021] Furthermore, the temperature of the constant temperature oscillation in step 2 is 30° C., the frequency is 50-70 rpm, and the time is 24 hours.

[0022] Furthermore, the specific test calculation method for the ratio of hydrophobic organic matter to hydrophilic organic matter in the extracellular polymer solution is: the extracellular polymer solution is passed through the XAD-8 and XAD-4 resins in series by a peristaltic pump to separate the hydrophilic organic matter and calculate its content a 1 , XAD-8 and XAD-4 resins were backwashed with sodium hydroxide solution to obtain hydrophobic organic acids and transitional hydrophilic organic acids, and the content of hydrophobic organic acids was calculated. 2 ; XAD-8 and XAD-4 resins were washed with methanol to obtain hydrophobic neutral organic matter and transitional hydrophilic neutral organic matter, and the content of hydrophobic neutral organic matter was calculated. 3 ;By a=(a 2 +a 3 ) / a 1 Calculate the ratio a of hydrophobic organic matter to hydrophilic organic matter.

[0023] Furthermore, the concentration of the sodium hydroxide solution is 0.1 mol / L.

[0024] Furthermore, the forward flushing flow rate is 30-40 mL / h, and the backwashing flow rate is 10-20 mL / h.

[0025] Furthermore, the test method for the protein content b, the polysaccharide content c, and the humic acid content d in the extracellular polymer solution is: prepare reagents sodium hydroxide-sodium carbonate mixed solution, copper sulfate pentahydrate solution, and sodium tartrate solution, mix the three solutions to prepare Lowry reagent 1, replace the copper sulfate pentahydrate solution with ultrapure water to prepare Lowry reagent 2, add Lowry reagents 1 and 2 to the extracellular polymer solution, then add Folin phenol solution, and measure the protein content b and humic acid content d; add phenol and concentrated sulfuric acid to the extracellular polymer solution in sequence to measure the polysaccharide content c;

[0026] Furthermore, in the sodium hydroxide-sodium carbonate mixed solution, the concentration of sodium hydroxide is 143 mmol / L, the concentration of sodium carbonate is 270 mmol / L, the concentration of copper sulfate pentahydrate solution is 57 mmol / L, and the concentration of sodium tartrate solution is 124 mmol / L.

[0027] Furthermore, the Lowry reagent 1 is prepared according to a volume ratio of 100:1:1 of a sodium hydroxide-sodium carbonate mixed solution, a copper sulfate pentahydrate solution, and a sodium tartrate solution.

[0028] Furthermore, the Lowry reagent 2 is prepared according to a volume ratio of 100:1:1 of a sodium hydroxide-sodium carbonate mixed solution, ultrapure water, and a sodium tartrate solution.

[0029] Furthermore, when the protein and humic acid contents were measured, the volume ratio of the extracellular polymer solution, Lowry reagent 1, Lowry reagent 2, and Folin phenol was 5:7:7:1.

[0030] Furthermore, when the polysaccharide is measured, the volume ratio of the extracellular polymer solution, the phenol solution with a mass percentage concentration of 5%, and the concentrated sulfuric acid with a mass percentage concentration of 98% is 2:1:5.

[0031] Furthermore, the method for testing the fluorescence intensity value e of tryptophan proteins and the fluorescence intensity value f of tyrosine proteins in the extracellular polymer solution is specifically as follows: ultrapure water is recorded as a blank spectrum, a three-dimensional fluorescence spectrum of the extracellular polymer solution is obtained by using a fluorescence spectrophotometer, and the DOMFluor toolbox in MATLAB R2014a is used to perform parallel factor modeling analysis on the processed fluorescence data to obtain the fluorescence intensity value e of tryptophan proteins and the fluorescence intensity value f of tyrosine proteins.

[0032] Furthermore, when the three-dimensional fluorescence of the extracellular polymer solution is measured, the excitation wavelength is set to 220-400 nm, the emission wavelength is set to 220-550 nm, and the step length is 5 nm.

[0033] Furthermore, the method for testing the ratio of α-helix g, the ratio of β-turn h, and the ratio of α-helix / (β-sheet + random coil) j of the protein secondary structure in the extracellular polymer solution is as follows: the extracellular polymer solution is freeze-dried and then the infrared spectrum is measured. The peak fit software is used to analyze the infrared spectrum at a wave number of 1600-1700 cm -1 The amide I band of the infrared spectrum was processed, and the proportion g of α-helix, k of β-fold, h of β-turn and m of random coil in the secondary structure of the protein were calculated according to the peak areas. The ratio j of α-helix / (β-fold+random coil) was calculated according to j=g / (k+m).

[0034] Furthermore, when analyzing the secondary structure of the protein, the wave number is 1600-1700cm -1 The method for processing the infrared spectrum amide I band is as follows: take the wave number of 1600-1700cm -1 The infrared spectrum amide I band was first baseline corrected, then deconvolved, and then fitted by the second-order derivative to obtain the fitting peak.

[0035] The physicochemical properties of extracellular polymers in sludge have a significant impact on the microstructure, rheological properties and water content of the sludge. For example, the gel-like network structure formed by the high molecular weight organic components in the extracellular polymers can effectively capture water, making the bound water more tightly bound to the sludge solid phase. In addition, the layered structure of the extracellular polymers is also closely related to the water content of the sludge. Loosely bound extracellular polymers help retain water in the floc pore structure. Therefore, the present invention uses the multiple characteristics of extracellular polymers to accurately identify the water content of the sludge, providing a basis for the targeted optimization of the sludge dewatering efficiency.

[0036] The hydrophilic and hydrophobic components in extracellular polymers are closely related to the water distribution characteristics of sludge. In particular, amphiphilic macromolecules represented by extracellular proteins play an important role in identifying and regulating the state of water occurrence, and their influence exceeds that of humic acid and polysaccharides. The reduction of hydrophilic proteins and the increase of hydrophobic tryptophan substances significantly promote the conversion of bound water to free water. In addition, the increase in the proportion of β-folded structures in extracellular polymers means that the protein structure is looser, which promotes the exposure of hydrophobic groups and improves the solid-liquid separation performance; on the contrary, more α-helical structures enhance the solid-water binding strength of sludge, which provides a strong basis for improving the dewaterability of sludge by regulating these dense structures. The present invention utilizes the extracellular polymer content, the ratio of hydrophobic organic matter to hydrophilic organic matter, the protein content, the polysaccharide content, the humic acid content, the fluorescence intensity value of tryptophan protein, the fluorescence intensity value of tyrosine protein, the α-helix ratio, the β-turn ratio, and the α-helix / (β-folding+random coil) ratio to quantitatively express the relationship between each parameter and the water occurrence state in the sludge, so that the water occurrence state in the sludge can be accurately identified, which is beneficial to optimizing the sludge dewatering efficiency.

[0037] The advantages of the present invention are as follows:

[0038] 1. Construct a functional index system based on the hydrophilic and hydrophobic components of extracellular polymers: Through the fine separation of hydrophilic and hydrophobic organic matter in sludge extracellular polymers, the polarity distribution, chemical composition, fluorescent components and molecular structure of the organic matter are fully characterized, and a set of functional index systems that accurately feedback the water content of sludge is established. Compared with traditional methods, this index system can more effectively and accurately distinguish and quantify the water content of sludge, and provide a new evaluation tool for the migration and transformation of water during sludge dehydration and its interaction with the EPS network.

[0039] 2. Significantly improve the accuracy of sludge dewatering performance detection: Starting from the hydrophilic and hydrophobic components of extracellular polymers, the distribution characteristics of free water, mechanically bound water and bound water in sludge are revealed, overcoming the uncertainty and limitations of traditional methods in defining water content. The method of the present invention for accurately separating the water component of extracellular polymers using low-field nuclear magnetic resonance technology is verified, indicating that the method of the present invention can achieve quantitative and refined analysis of the water content of sludge, greatly improve the detection accuracy of sludge dewatering performance, and provide reliable technical support for the precise control of the sludge dewatering process.

[0040] 3. Provide scientific basis for targeted optimization of sludge dewatering technology: Based on the comprehensive characterization and functional analysis of the hydrophilic and hydrophobic components of extracellular polymers, the intrinsic relationship between the sludge moisture state and the multiple characteristics of extracellular polymers is established, and the key components and structures that determine the distribution characteristics and migration and transformation of different forms of water in sludge are identified. Through targeted regulation of these key parameters, scientific basis and data support can be provided for the optimization of sludge dewatering process, promoting the development of sludge treatment technology towards a more efficient, intelligent and precise direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a curve diagram showing the relationship between free water and total organic carbon content in Example 1;

[0042] Figure 2 is a curve diagram showing the relationship between bound water and total organic carbon content in Example 1;

[0043] Figure 3 is a curve diagram showing the relationship between free water and the ratio a of hydrophobic organic matter to hydrophilic organic matter in Example 2;

[0044] Figure 4 is a curve diagram showing the relationship between the ratio a of bound water to hydrophobic organic matter to hydrophilic organic matter in Example 2;

[0045] Figure 5 is a curve diagram showing the relationship between the free water content and the protein content b in Example 3;

[0046] Figure 6 is a curve diagram showing the relationship between the bound water content and the protein content b in Example 3;

[0047] Figure 7 is a curve diagram showing the relationship between the free water content and the polysaccharide content c in Example 3;

[0048] Figure 8 is a curve diagram showing the relationship between bound water and the content c of polysaccharide in Example 3;

[0049] Fig. 9 is a relationship curve diagram of the content d of free water and humic acid in Example 3;

[0050] Fig.10 is a curve diagram showing the relationship between the content d of bound water and humic acid in Example 3;

[0051] Fig.11 is a curve diagram showing the relationship between the fluorescence intensity value e of free water and tryptophan protein in Example 4;

[0052] Fig.12 is a curve diagram showing the relationship between the fluorescence intensity value e of bound water and tryptophan protein in Example 4;

[0053] Fig.13 is a curve diagram showing the relationship between the fluorescence intensity value f of free water and tyrosine protein in Example 4;

[0054] Fig.14 is a curve diagram showing the relationship between the fluorescence intensity value f of bound water and tyrosine-based proteins in Example 4;

[0055] Fig.15 is a curve diagram showing the relationship between the ratio g of free water and the α-helix of the secondary structure of the protein in Example 5;

[0056] Fig.16 is a curve diagram showing the relationship between the ratio g of bound water and the α-helix of the secondary structure of the protein in Example 5;

[0057] Fig.17 is a curve diagram showing the relationship between the ratio h of free water and the β-turn of the protein secondary structure in Example 5;

[0058] Fig.18 is a curve diagram showing the relationship between the ratio h of bound water and the β-turn of the protein secondary structure in Example 5;

[0059] Fig.19 is a curve diagram showing the relationship between free water and the ratio j of α-helix / (β-sheet+random coil) in the secondary structure of the protein in Example 5;

[0060] Fig. 20 This is a curve diagram showing the relationship between bound water and the ratio j of α-helix / (β-sheet + random coil) in the secondary structure of the protein in Example 5. DETAILED DESCRIPTION

[0061] The beneficial effects of the present invention are verified by the following examples.

[0062] Example 1: The method of using extracellular polymers to identify the water content of urban sludge in this example is carried out according to the following steps:

[0063] 1. Take six kinds of sludge from the secondary sedimentation tank of a municipal sewage treatment plant, store them in a refrigerator at 4°C for 24 hours, then place the precipitated sludge in a centrifuge for centrifugal separation at a speed of 4000g, discard the supernatant after centrifugation, take the sludge precipitate at the bottom of the centrifuge tube as a test sample, and obtain six test samples; perform low-field nuclear magnetic resonance measurement on the six test samples to obtain the relative contents of free water, mechanically bound water, and chemically bound water;

[0064] 2. Add ammonia water to the test sample, with the ratio of sludge sediment to ammonia water being 1g:2mL, place it in a shaker and shake it at a constant temperature of 30°C, a frequency of 60rpm, and a time of 24h. Take the supernatant, which is the extracellular polymer solution;

[0065] 3. Test the total organic carbon content of the extracellular polymer solution. The total organic carbon content is represented by x, and the unit is mg / gVS. The total organic carbon content is used as the horizontal marker, and the free water content of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical marker. The test data of each test sample is plotted on Figure 1 The relationship between free water and total organic carbon content is obtained by fitting, and the fitting curve is y 1 =-0.0147x+5.4537, R 2 =0.7702; the total organic carbon content is used as the horizontal mark, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical mark, and the test data of each test sample is plotted on Figure 2 The relationship between chemically bound water and total organic carbon content is fitted as y 2 =0.0185x+1.0302, R 2 =0.6922. This indicates that the total organic carbon content in the extracellular polymers is strongly correlated with the ratio of free water to bound water in the sludge, that is, the extracellular polymer content has a high degree of accuracy in defining and identifying free water and bound water in the sludge. By measuring the total organic carbon content of the extracellular polymer solution, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture storage state and the content of mechanically bound water in urban sludge.

[0066] Example 2: The method of using extracellular polymers to identify the water content of urban sludge in this example is carried out according to the following steps:

[0067] 1. Take six kinds of sludge from the secondary sedimentation tank of a municipal sewage treatment plant, store them in a refrigerator at 4°C for 24 hours, then place the precipitated sludge in a centrifuge for centrifugal separation at a speed of 4000g, discard the supernatant after centrifugation, take the sludge precipitate at the bottom of the centrifuge tube as a test sample, and obtain six test samples; perform low-field nuclear magnetic resonance measurement on the six test samples to obtain the relative contents of free water, mechanically bound water, and chemically bound water;

[0068] 2. Add ammonia water to the test sample, with the ratio of sludge sediment to ammonia water being 1g:2mL, place it in a shaker and shake it at a constant temperature of 30°C, a frequency of 60rpm, and a time of 24h. Take the supernatant, which is the extracellular polymer solution;

[0069] 3. Test the ratio of hydrophobic organic matter to hydrophilic organic matter in the extracellular polymer solution: Use a peristaltic pump to pass the extracellular polymer solution through the series-connected XAD-8 and XAD-4 resins to separate the hydrophilic organic matter and calculate its content. 1 , XAD-8 and XAD-4 resins were backwashed independently with 0.1 mol / L sodium hydroxide solution at a flow rate of 15 mL / h to obtain hydrophobic organic acids and transitional hydrophilic organic acids, and the content of hydrophobic organic acids was calculated. 2 ; Use methanol at a flow rate of 35mL / h to flush XAD-8 and XAD-4 resins to obtain hydrophobic neutral organic matter and transitional hydrophilic neutral organic matter, and calculate the content of hydrophobic neutral organic matter a 3 ;By a=(a 2 +a 3 ) / a 1 Calculate the ratio a of hydrophobic organic matter to hydrophilic organic matter; plot the test data of each test sample on the graph with the ratio a of hydrophobic organic matter to hydrophilic organic matter as the horizontal marker and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 as the vertical marker. Figure 3 The relationship between free water and the ratio of hydrophobic organic matter to hydrophilic organic matter a is obtained by fitting, and the fitting curve is y 1 =1.0268a+0.8918, R 2 =0.8245; the ratio of hydrophobic organic matter to hydrophilic organic matter a is used as the horizontal marker, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical marker, and the test data of each test sample is plotted on Figure 4 The relationship between chemically bound water and the ratio of hydrophobic organic matter to hydrophilic organic matter is fitted as y 2 =-1.3946a+6.9884, R 2 =0.8658; This indicates that the ratio of hydrophobic organic matter to hydrophilic organic matter a is strongly correlated with the ratio of free water to bound water in sludge, that is, the ratio of hydrophobic organic matter to hydrophilic organic matter in extracellular polymers a has a high accuracy in defining and identifying free water and bound water in sludge. By measuring the ratio of hydrophobic organic matter to hydrophilic organic matter in extracellular polymer solution a, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0070] Example 3: The method of using extracellular polymers to identify the water content of urban sludge in this example is carried out according to the following steps:

[0071] 1. Take six kinds of sludge from the secondary sedimentation tank of a municipal sewage treatment plant, store them in a refrigerator at 4°C for 24 hours, then place the precipitated sludge in a centrifuge for centrifugal separation at a speed of 4000g, discard the supernatant after centrifugation, take the sludge precipitate at the bottom of the centrifuge tube as a test sample, and obtain six test samples; perform low-field nuclear magnetic resonance measurement on the six test samples to obtain the relative contents of free water, mechanically bound water, and chemically bound water;

[0072] 2. Add ammonia water to the test sample, with the ratio of sludge sediment to ammonia water being 1g:2mL, place it in a shaker and shake it at a constant temperature of 30°C, a frequency of 60rpm, and a time of 24h. Take the supernatant, which is the extracellular polymer solution;

[0073] 3. Determination of the protein content b, polysaccharide content c, humic acid content d in the extracellular polymer solution: prepare sodium hydroxide-sodium carbonate mixed solution, copper sulfate pentahydrate solution, and sodium tartrate solution, wherein the sodium hydroxide concentration in the sodium hydroxide-sodium carbonate mixed solution is 143mmol / L, the sodium carbonate concentration is 270mmol / L, the copper sulfate pentahydrate solution concentration is 57mmol / L, and the sodium tartrate solution concentration is 124mmol / L; mix the above three solutions according to the volume ratio of sodium hydroxide-sodium carbonate mixed solution, copper sulfate pentahydrate solution, and sodium tartrate solution of 100:1:1 to prepare Lowry reagent 1; mix the sodium hydroxide-sodium carbonate mixed solution, copper sulfate pentahydrate solution, and sodium tartrate solution according to the volume ratio of 100:1:1 to prepare Lowry reagent 1; The volume ratio of sodium chloride-sodium carbonate mixed solution, ultrapure water and sodium tartrate solution is 100:1:1 to prepare Lowry reagent 2; according to the volume ratio of extracellular polymer solution, Lowry reagent 1, Lowry reagent 2 and folin phenol being 5:7:7:1, Lowry reagent 1 and 2 are added to the extracellular polymer solution respectively, and then folin phenol solution is added to determine the protein content b and humic acid content d; according to the volume ratio of extracellular polymer solution, phenol solution with a mass percentage concentration of 5% and concentrated sulfuric acid with a mass percentage concentration of 98% being 2:1:5, phenol and concentrated sulfuric acid are added to the extracellular polymer solution successively to determine the polysaccharide content c;

[0074] The protein content b in the extracellular polymer solution is plotted horizontally, and the free water content of the six test samples measured by low-field nuclear magnetic resonance in step 1 is plotted vertically. Figure 5 The relationship between free water and protein content b is obtained by fitting. 1 =0.0333b+1.6203, R 2 =0.7514; the protein content b in the extracellular polymer solution is used as the horizontal marker, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical marker, and the test data of each test sample is plotted on Figure 6The relationship between chemically bound water and protein content b is fitted as y 2 =-0.0484b+6.1425, R 2 =0.9044; This indicates that the protein content b in the extracellular polymer solution has a strong correlation with the ratio of free water to bound water in the sludge. By measuring the protein content b in the extracellular polymer solution, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0075] The test data of each test sample are plotted on the graph with the polysaccharide content c as the horizontal marker and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 as the vertical marker. Figure 7 The relationship between free water and polysaccharide content c was obtained by fitting, and the fitting curve was y1 = -0.0874c + 5.8395, R 2 =0.7419; the polysaccharide content c is used as the horizontal marker, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical marker, and the test data of each test sample is plotted on Figure 8 The relationship between chemically bound water and the content c of polysaccharides is fitted as y 2 =0.1241c+0.0986, R 2 =0.8523; This indicates that the content of polysaccharides c in the extracellular polymer solution has a strong correlation with the ratio of free water to bound water in the sludge. By measuring the content of polysaccharides c in the extracellular polymer solution, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0076] The test data of each test sample are plotted on the graph with the content of humic acid in the extracellular polymer solution d as the horizontal marker and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 as the vertical marker. Fig. 9 The relationship between free water and humic acid content d is obtained by fitting, and the fitting curve is y 1= -0.0119d+4.0989, R 2=0.7896; the content of humic acid in the extracellular polymer solution d is used as the horizontal mark, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical mark, and the test data of each test sample is plotted on Fig.10 The relationship between chemically bound water and humic acid content d is fitted as y 2 =0.0155d+2.6871, R 2 =0.7628; This indicates that the content of humic acid d in the extracellular polymer solution has a strong correlation with the ratio of free water to bound water in the sludge. By measuring the content of humic acid d in the extracellular polymer solution, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0077] Example 4: The method of using extracellular polymers to identify the water content of urban sludge in this example is carried out according to the following steps:

[0078] 1. Take six kinds of sludge from the secondary sedimentation tank of a municipal sewage treatment plant, store them in a refrigerator at 4°C for 24 hours, then place the precipitated sludge in a centrifuge for centrifugal separation at a speed of 4000g, discard the supernatant after centrifugation, take the sludge precipitate at the bottom of the centrifuge tube as a test sample, and obtain six test samples; perform low-field nuclear magnetic resonance measurement on the six test samples to obtain the relative contents of free water, mechanically bound water, and chemically bound water;

[0079] 2. Add ammonia water to the test sample, with the ratio of sludge sediment to ammonia water being 1g:2mL, place it in a shaker and shake it at a constant temperature of 30°C, a frequency of 60rpm, and a time of 24h. Take the supernatant, which is the extracellular polymer solution;

[0080] 3. Test the fluorescence intensity value e of tryptophan proteins and the fluorescence intensity value f of tyrosine proteins in the extracellular polymer solution. The specific method is: record ultrapure water as a blank spectrum, use a fluorescence spectrophotometer to test the three-dimensional fluorescence spectrum of the extracellular polymer solution under the conditions of excitation wavelength of 220-400nm, emission wavelength of 220-550nm, and step length of 5nm, use the DOMFluor toolbox in MATLAB R2014a to perform parallel factor modeling analysis on the processed fluorescence data, and obtain the fluorescence intensity value e of tryptophan proteins and the fluorescence intensity value f of tyrosine proteins;

[0081] The fluorescence intensity value e of tryptophan protein is plotted horizontally and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is plotted vertically. Fig.11 The relationship between the fluorescence intensity value e of free water and tryptophan protein is obtained by fitting, and the fitting curve is y 1 =-0.0262e+5.8598, R 2 =0.7668; the fluorescence intensity value e of tryptophan protein is used as the horizontal mark, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical mark, and the test data of each test sample is plotted on Fig.12 The relationship between chemically bound water and the fluorescence intensity value e of tryptophan proteins is fitted as y 2 =0.0362e+0.1727, R 2 =0.835; This indicates that the fluorescence intensity value e of tryptophan proteins in the extracellular polymer solution has a strong correlation with the ratio of free water to bound water in the sludge. By measuring the fluorescence intensity value e of tryptophan proteins in the extracellular polymer solution, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0082] The fluorescence intensity value f of tyrosine protein is plotted horizontally and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is plotted vertically. Fig.13 The relationship between the fluorescence intensity value f of free water and tyrosine protein is obtained by fitting, and the fitting curve is y 1= 0.0569f+1.1071, R 2 =0.8669; the fluorescence intensity value f of tyrosine protein is used as the horizontal mark, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical mark, and the test data of each test sample is plotted on Fig.14 The relationship between chemically bound water and the fluorescence intensity value f of tyrosine proteins is fitted as y 2 =-0.072f+6.5101, R 2 =0.7905; This indicates that the fluorescence intensity value f of tyrosine proteins in the extracellular polymer solution has a strong correlation with the ratio of free water to bound water in the sludge. By measuring the fluorescence intensity value f of tyrosine proteins in the extracellular polymer solution, the free water content y can be obtained according to the relationship 1, chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0083] Example 5: The method of using extracellular polymers to identify the water content of urban sludge in this example is carried out according to the following steps:

[0084] 1. Take six kinds of sludge from the secondary sedimentation tank of a municipal sewage treatment plant, store them in a refrigerator at 4°C for 24 hours, then place the precipitated sludge in a centrifuge for centrifugal separation at a speed of 4000g, discard the supernatant after centrifugation, take the sludge precipitate at the bottom of the centrifuge tube as a test sample, and obtain six test samples; perform low-field nuclear magnetic resonance measurement on the six test samples to obtain the relative contents of free water, mechanically bound water, and chemically bound water;

[0085] 2. Add ammonia water to the test sample, with the ratio of sludge sediment to ammonia water being 1g:2mL, place it in a shaker and shake it at a constant temperature of 30°C, a frequency of 60rpm, and a time of 24h. Take the supernatant, which is the extracellular polymer solution;

[0086] 3. The method for testing the ratio of α-helix g, the ratio of β-turn h, and the ratio of α-helix / (β-sheet + random coil) j of the secondary structure of protein in the extracellular polymer solution is as follows: freeze-dry the extracellular polymer solution and measure the infrared spectrum. Use Peakfit software to analyze the infrared spectrum at a wave number of 1600-1700 cm -1 The infrared spectrum amide I band was first baseline corrected, deconvoluted, and then fitted by the second-order derivative to obtain the fitting peak. The proportion g of α-helix, the proportion k of β-fold, the proportion h of β-turn, and the proportion m of random coil in the secondary structure of the protein were calculated according to the peak area, and the ratio j of α-helix / (β-fold+random coil) was calculated according to j=g / (k+m);

[0087] The test data of each test sample are plotted on the graph with the ratio g of the α-helix of the protein secondary structure as the horizontal marker and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 as the vertical marker. Fig.15 The relationship between the ratio of free water and α-helix g is obtained by fitting as y 1 =-0.1335g+5.9203, R 2 =0.8063; the ratio g of the α-helix of the secondary structure of the protein is used as the horizontal mark, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical mark, and the test data of each test sample is plotted on Fig.16The relationship between the chemically bound water and the ratio g of the α-helix is ​​fitted as y 2 =0.1716g+0.362, R 2 =0.7588; This indicates that the ratio g of the secondary structure α-helix of protein in the extracellular polymer solution is strongly correlated with the ratio of free water to bound water in the sludge. By measuring the ratio g of the secondary structure α-helix of protein in the extracellular polymer solution, the free water content y can be obtained according to the relationship. 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0088] The test data of each test sample are plotted on the graph with the ratio of the β-turn angle of the protein secondary structure h as the horizontal mark and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 as the vertical mark. Fig.17 The relationship between the ratio of free water and β-turn angle h is obtained by fitting, and the fitting curve is y 1 =-0.1794h+7.093, R 2 =0.0.8917; the ratio of the β-turn angle of the protein secondary structure h is used as the horizontal mark, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical mark, and the test data of each test sample is plotted on Fig.18 The relationship between the chemically bound water and the β-turn ratio h is shown in the figure y 2 =0.2241h-1.0014, R 2 =0.7924; This indicates that the ratio of β-turns of the secondary structure of proteins in the extracellular polymer solution h is strongly correlated with the ratio of free water to bound water in the sludge. By measuring the ratio of β-turns of the secondary structure of proteins in the extracellular polymer solution h, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

[0089] The test data of each test sample are plotted on the graph with the ratio j of α-helix / (β-sheet + random coil) in the secondary structure of the protein in the extracellular polymer solution as the horizontal marker and the free water of the six test samples measured by low-field nuclear magnetic resonance in step 1 as the vertical marker. Fig.19The relationship between free water and the ratio of α-helix / (β-sheet + random coil) j is obtained by fitting as y 1= -4.0478j+4.7488, R 2 =0.8494; the ratio j of α-helix / (β-folding + random coil) in the secondary structure of protein in the extracellular polymer solution is used as the horizontal marker, and the chemically bound water of the six test samples measured by low-field nuclear magnetic resonance in step 1 is used as the vertical marker, and the test data of each test sample is plotted on Fig. 20 The relationship between chemically bound water and the ratio j of α-helix / (β-sheet + random coil) is fitted as y 2 =4.7323j+2.0585, R 2 =0.6608; This indicates that the ratio j of the secondary structure of protein α-helix / (β-folding + random coiling) in the extracellular polymer solution has a strong correlation with the ratio of free water to bound water in the sludge. By measuring the ratio j of the secondary structure of protein α-helix / (β-folding + random coiling) in the extracellular polymer solution, the free water content y can be obtained according to the relationship 1 , chemically bound water content 2 , and then use y 3 =100-y 1 -y 2 Calculation of mechanically bound water 3 , thus knowing the moisture status of urban sludge.

Claims

1. A method for identifying the water content of urban sludge using extracellular polymers, characterized in that: The method proceeds as follows:

1. Take the sludge from the secondary sedimentation tank of the urban sewage treatment plant, store it in a refrigerator at 4℃ and let it settle for 24 to 72 hours, then centrifuge the settled sludge, discard the supernatant, and take the sludge sediment at the bottom of the centrifuge tube as the test sample; 2. Add ammonia water to the test sample, place it in a shaker and shake at a constant temperature, and take the supernatant, which is the extracellular polymer solution; 3. Test the total organic carbon content of the extracellular polymer solution. The total organic carbon content is represented by x, and the unit is mg / g VS. The free water content in the urban sludge is calculated according to y1=-0.0147x+5.4537, where y1 represents the free water content, and the unit is %; the chemically bound water content in the urban sludge is calculated according to y2=0.0185x+1.0302, where y2 represents the chemically bound water content, and the unit is %; the mechanically bound water content in the urban sludge is calculated according to y3=100-y1-y2, where y3 represents the mechanically bound water content, so as to know the water storage state of the urban sludge; Alternatively, the ratio of hydrophobic organic matter to hydrophilic organic matter in the extracellular polymer solution is tested, and the ratio of hydrophobic organic matter to hydrophilic organic matter is represented by a, which is dimensionless; the content of free water in urban sludge is calculated according to y1=1.0268a+0.8918, wherein y1 represents the content of free water, and the unit is %; the content of chemically bound water in urban sludge is calculated according to y2=-1.3946a+6.9884, wherein y2 represents the content of chemically bound water, and the unit is %; the content of mechanically bound water in urban sludge is calculated according to y3=100-y1-y2, wherein y3 represents the content of mechanically bound water, thereby obtaining the moisture occurrence state of urban sludge; Alternatively, the protein content b in the extracellular polymer solution is tested, in units of mg / g VS; the free water content in the urban sludge is calculated according to y1=0.0333b+1.6203, where y1 represents the free water content, in units of %; the chemically bound water content in the urban sludge is calculated according to y2=-0.0484b+6.1425, where y2 represents the chemically bound water content, in units of %; the mechanically bound water content in the urban sludge is calculated according to y3=100-y1-y2, where y3 represents the mechanically bound water content, thereby obtaining the moisture occurrence state of the urban sludge; Alternatively, the content of polysaccharides in the extracellular polymer solution is tested, c, in mg / g VS; the content of free water in urban sludge is calculated according to y1=-0.0874c+5.8395, where y1 represents the content of free water, in %; the content of chemically bound water in urban sludge is calculated according to y2=0.1241c+0.0986, where y2 represents the content of chemically bound water, in %; the content of mechanically bound water in urban sludge is calculated according to y3=100-y1-y2, where y3 represents the content of mechanically bound water, thereby knowing the moisture occurrence state of urban sludge; Alternatively, the content of humic acid in the test extracellular polymer solution is measured in mg / g VS; the content of free water in the municipal sludge is measured in y 1= -0.0119d+4.0989, where y1 represents the content of free water, in %; the content of chemically bound water in urban sludge is calculated as y2=0.0155d+2.6871, where y2 represents the content of chemically bound water, in %; the content of mechanically bound water in urban sludge is calculated as y3=100-y1-y2, where y3 represents the content of mechanically bound water, thus knowing the moisture state of urban sludge; Alternatively, the fluorescence intensity value e of the tryptophan-based protein in the test extracellular polymer solution is dimensionless; The free water content in urban sludge is calculated as y1=-0.0262e+5.8598, where y1 represents the free water content in %; the chemically bound water content in urban sludge is calculated as y2=0.0362e+0.1727, where y2 represents the chemically bound water content in %; the mechanically bound water content in urban sludge is calculated as y3=100-y1-y2, where y3 represents the mechanically bound water content, thereby obtaining the moisture state of urban sludge; Alternatively, the fluorescence intensity value f of tyrosine proteins in the test extracellular polymer solution is dimensionless; the free water content in urban sludge is expressed as y 1= 0.0569f+1.1071, where y1 represents the content of free water, in %; the content of chemically bound water in urban sludge is calculated as y2=-0.072f+6.5101, where y2 represents the content of chemically bound water, in %; the content of mechanically bound water in urban sludge is calculated as y3=100-y1-y2, where y3 represents the content of mechanically bound water, thus knowing the moisture state of urban sludge; Alternatively, the proportion of α-helix of the protein secondary structure in the extracellular polymer solution is tested, g, in %; the free water content in the urban sludge is calculated according to y1=-0.1335g+5.9203, where y1 represents the free water content, in %; the chemically bound water content in the urban sludge is calculated according to y2=0.1716g+0.362, where y2 represents the chemically bound water content, in %; the mechanically bound water content in the urban sludge is calculated according to y3=100-y1-y2, where y3 represents the mechanically bound water content, thereby obtaining the moisture state of the urban sludge; Alternatively, the ratio of the β-turn of the protein secondary structure in the extracellular polymer solution is tested, h, in %; the free water content in the urban sludge is calculated according to y1=-0.1794h+7.093, where y1 represents the free water content, in %; the chemically bound water content in the urban sludge is calculated according to y2=0.2241h-1.0014, where y2 represents the chemically bound water content, in %; the mechanically bound water content in the urban sludge is calculated according to y3=100-y1-y2, where y3 represents the mechanically bound water content, thereby obtaining the moisture state of the urban sludge; Alternatively, the ratio of α-helix / (β-sheet + random coil) in the secondary structure of proteins in the test extracellular polymer solution is j, dimensionless; the free water content in urban sludge is y 1= -4.0478j+4.7488, where y1 represents the content of free water, in %; the content of chemically bound water in urban sludge is calculated as y2=4.7323j+2.0585, where y2 represents the content of chemically bound water, in %; the content of mechanically bound water in urban sludge is calculated as y3=100-y1-y2, where y3 represents the content of mechanically bound water, thereby knowing the moisture occurrence state of urban sludge.

2. The method for identifying the water content of urban sludge using extracellular polymers according to claim 1, characterized in that: The centrifugal separation in step 1 has a rotation speed of 3000-5000g.

3. The method for identifying the water content of urban sludge using extracellular polymers according to claim 1 or 2, characterized in that: In step 2, the ratio of sludge precipitate to ammonia water with a mass percentage concentration of 24% to 26% is 1g: (1 to 3)mL.

4. The method for identifying the water content of urban sludge by using extracellular polymers according to claim 1 or 2, characterized in that: The temperature of the constant temperature oscillation in step 2 is 30° C., the frequency is 50-70 rpm, and the time is 24 h.

5. The method for identifying the water content of urban sludge by using extracellular polymers according to claim 1 or 2, characterized in that: The specific test calculation method for the ratio a of hydrophobic organic matter to hydrophilic organic matter in the extracellular polymer solution described in step 3 is: the extracellular polymer solution is passed through the XAD-8 and XAD-4 resins connected in series with a peristaltic pump to separate the hydrophilic organic matter and calculate its content a1; the XAD-8 and XAD-4 resins are independently backwashed with sodium hydroxide solution to obtain hydrophobic organic acids and transitional hydrophilic organic acids, and the content a2 of the hydrophobic organic acid is calculated; the XAD-8 and XAD-4 resins are respectively forward washed with methanol to obtain hydrophobic neutral organic matter and transitional hydrophilic neutral organic matter, and the content a3 of the hydrophobic neutral organic matter is calculated; the ratio a of hydrophobic organic matter to hydrophilic organic matter is calculated by a=(a2+a3) / a1.

6. The method for identifying the water content of urban sludge by using extracellular polymers according to claim 5, characterized in that: The forward flushing flow rate is 30-40 mL / h, and the backwashing flow rate is 10-20 mL / h.

7. The method for identifying the water content of urban sludge using extracellular polymers according to claim 1 or 2, characterized in that: The test method for the protein content b, polysaccharide content c, and humic acid content d in the extracellular polymer solution is as follows: prepare reagents of sodium hydroxide-sodium carbonate mixed solution, copper sulfate pentahydrate solution, and sodium tartrate solution, mix the three solutions to prepare Lowry reagent 1, replace the copper sulfate pentahydrate solution with ultrapure water to prepare Lowry reagent 2, add Lowry reagent 1 and 2 to the extracellular polymer solution respectively, then add Folin phenol solution, and measure the protein content b and humic acid content d; Phenol and concentrated sulfuric acid were added to the extracellular polymer solution successively to determine the polysaccharide content c.

8. The method for identifying the water content state of urban sludge by using extracellular polymers according to claim 1 or 2, characterized in that: The method for testing the fluorescence intensity value e of tryptophan proteins and the fluorescence intensity value f of tyrosine proteins in an extracellular polymer solution is specifically as follows: ultrapure water is recorded as a blank spectrum, a three-dimensional fluorescence spectrum of the extracellular polymer solution is obtained by a fluorescence spectrophotometer, and the DOMFluor toolbox in MATLAB R2014a is used to perform parallel factor modeling analysis on the processed fluorescence data to obtain the fluorescence intensity value e of tryptophan proteins and the fluorescence intensity value f of tyrosine proteins.

9. The method for identifying the water content state of urban sludge by using extracellular polymers according to claim 1 or 2, characterized in that: The method for testing the ratio of α-helix g, the ratio of β-turn h, and the ratio of α-helix / (β-sheet + random coil) j of the secondary structure of protein in the extracellular polymer solution is as follows: freeze-dry the extracellular polymer solution and measure the infrared spectrum, and use Peakfit software to analyze the infrared spectrum at a wave number of 1600-1700cm -1 The amide I band of the infrared spectrum was processed, and the proportion g of α-helix, k of β-fold, h of β-turn and m of random coil in the secondary structure of the protein were calculated according to the peak areas. The ratio j of α-helix / (β-fold+random coil) was calculated according to j=g / (k+m).

10. The method for identifying the water content state of urban sludge by using extracellular polymers according to claim 9, characterized in that: The protein secondary structure analysis is performed at a wave number of 1600-1700 cm -1 The method for processing the infrared spectrum amide I band is as follows: take the wave number of 1600-1700cm -1 The infrared spectrum amide I band was first baseline corrected, then deconvolved, and then fitted by the second-order derivative to obtain the fitting peak.